Didactic Proposal to Include Nanoscience and Nanotechnology at High School Curriculum Linking Physics, Chemistry and Biology - Baltazar-Rojas, S; Tecpan-Flores, S (Institute of Physics Publishing, 2018)
Science and technology at the nanoscale is an important field, not only in modern science, but also an economic activity of vertiginous growth, and therefore, nanoscience should be included as a solid part of the educational curriculum. An interdisciplinary didactic proposal is presented to incorporate nanoscience and nanotechnology (N&N) at the current Chilean high school curriculum. Throughout the didactic sequence, it is expected a better understanding of the science courses followed by the students and, at the same time, of the fundamental concepts of N&N, identifying their benefits and risks to the society with a critical view. This article presents the steps followed in the design of the didactic proposal and characteristics of the learning activities, as well as the methodology foreseen for its validation. Possible risks for the implementation of the proposal are discussed. © Published under licence by IOP Publishing Ltd.